Kinerja Keuangan Perbankan BEI Ditinjau dari Aspek Good Corporate Governance dan Ukuran Perusahaan - Angga Syahputra; Ismaulina Ismaulina; Heny Rofizar (Widya Cipta - Jurnal Sekretari dan Manajemen, 2022)
This study discusses cases and economic problems that arise from inappropriate applications, then the existence of diverse ownership structures and company sizes that can affect managers in reporting company performance. The purpose of this study was to determine the effect of the implementation of Good Corporate Governance (GCG), Company Size, either partially or simultaneously on the Financial Performance of Banks listed on the Indonesia Stock Exchange in 2014-2018. The research method used is quantitative data analysis using multiple linear regression analysis method. The data used in this study is secondary data obtained from financial reports obtained through the IDX website. The results of the study that the GCG variable did not have a positive and significant effect on the financial performance of the bank was found with the value of t count < t table (-0.771 < 2.002). Firm size variable has a positive effect on bank financial performance with the acquisition of t count > t table (46,335 > 2,002). Simultaneously using the F test, it was found that the GCG variable and company size had an effect on the financial performance of banks listed on the Indonesia Stock Exchange for the 2014-2018 period.